Types and Outcomes of Diagnostic Measures provided for women Presented with Postmenopausal Bleeding - Elsammani, Malaz; Elhawari, Sahar; Murad, Gawahir; Nasr, Khairi; Abdelgader, Alla; Suliman, Hajar; Abuobida, Baharelden; Abdeen, Bashir; Abdelwahid, Awadalla (Clinical Journal of Obstetrics and Gynecology, 2025)
Background: Postmenopausal bleeding (PMB) is bleeding from the genital tract after 12 months of amenorrhea in a woman over the age of 50, or 24 months if below the age of 50 years, in 10% of women presented with PMB, the cause is endometrial cancer. Purpose: To assess the clinical presentation types and outcomes of diagnostic measures provided for women presenting with PMB at Saad Abu-Alela Hospital, Khartoum, Sudan. Methodology: It was a descriptive, cross-sectional study conducted at Saad Abu-Alela Teaching Hospital in the period from January to December 2022. An interview questionnaire was used for data collection. Fifty-nine (59) postmenopausal women were included in this study, age, parity, risk factors, duration of bleeding, duration of menopause, ultrasound findings, and hysteroscopy findings were recorded. Results: The majority of study participants were aged between 50-54 years, menopause duration was most 1-4 years, most of the participants were educated and medically free, DM and HTN, and most of the participants were multiparous. Duration of PMB ranged between weeks in a third of cases and up to more than a year in some cases, amount of bleeding was mild in more than half. Ultrasound is used to assess the endometrial thickness and other findings, also hysteroscopy and biopsy or Dilation and curettage and hysterectomy. Conclusion: The ultrasound and endometrial biopsy via inpatient hysteroscopy and dilatation and curettage were the best tools for evaluation of (PMB), benign conditions were the most frequent outcome and endometrial cancer.